Gamelan Kutai Sebagai Iringan Tari Ganjur Di Kesultanan Kutai Kartanegara Kalimantan Timur - Suprayedno (FSP ISI Yogyakarta, 2016)
Traditional musics from everyculture inherited by the ancestors of every ethnic group makes the personality traits and also becomes an identity of each tribes. One of them, gamelan which exists in sultanate of Kutai Kartanegara (Kutai Kartanegara Kingdom) located in Tenggarong District, Kutai Kartanegara Regency in East Kalimantan Province. Kutainese gamelan is derived from Javanese cultureacculturation. It has been used from hundreds years ago in the sultanate of Kutai Kartanegara’s political order. It becomes a proof of sultanate Kutai Kartanegara’s legacy which still exists in the royal sphere by keeping its sanctity and its function and role on the royal order. Kutainese gamelanis usually used for traditional rituals and some other activities in the sultanate Kutai Kartanegra, such as; Erau traditional ceremony, accompanimentsultanateclassical dance, the appointment of the new Sultan, the royal wedding, and welcoming performance for king’s guests. Righteously according to the Erau traditional ceremonies, Kutaniese gamelan should be performed as an accompaniment of Ganjur Dance. In particularly during the bepalas event; an ancient demand ceremony for salvation of the entire a series of the ceremonies. The instrumentation of Kutainese gamelan is consist of a set of slendro gamelan; bonang, gambang, slenthem, kendang, demung, saron, peking, kethuk, kenong, kempul, gong. Which as an addition Kutainese gamelan uses his own musical and compositional methods. Therefore based on this fact, Kutainese gamelan is considered of having differences in musical approaches; compositional, structure, and form. In compared with his fellow Javenese gamelan.